AMAtI (Archivio Multimendiale Attori Italiani) - Siro Ferrone Francesca Simoncini (Electronica, 2012)
The Archivio Multimediale degli Attori Italiani (AMAtI) is an on-line computerized archive devoted to the Italian actors, dancers and singers who have practised the profession from the fifteenth to the twenty-first century. For every actor AMAtI offers a complete original and up-to-date profile, bibliography, list of sources, and a detailed selection of data on his/her career and single performances. Documents, images and multi-media material (video and audio), linked to the collected information, can be viewed in order to provide a more in-depth rundown on each actor. It is also possible to research single performances independently, how characters have been interpreted over time, as well as theatre companies and historical theatres.